PENGEMBANGAN ASPEK SOSIAL ANAK USIA DINI PERSPEKTIF MARIA MONTESSORI DALAM BUKU THE ABSORBENT MIND - Ali, Musyafa; Fadilah , Iskhulatin; Triyana; Apriliani , Elina Intan (IKIP Siliwangi, 2025)
Maria Montessori's thoughts on early childhood education have had a tremendous impact on educators and observers of early childhood development. Maria Montessori developed many theories from various experiences she had while running Casa Dei Bambini, or the children's house, at that time. One of the theories she put forward from her experience was the theory of children's social development. The purpose of this study is to examine the results of Maria Montessori's thoughts related to aspects of social development that she has put forward in her book entitled The Absorbent Mind. This research is library research. The data source in this study is a book by Maria Montessori entitled The Absorbent Mind. The data collection technique used by the researcher in this study is documentation in the form of previous literature, both research and theory. The data analysis technique used is content analysis, where the researcher will reveal the contents of a book that describes the situation of the researcher and his community at the time the book was written. The results of this study show that the aspects of social development developed by Maria Montessori, as stated in her book The Absorbent Mind, are respect, patience, friendship and mutual affection, independence, mutual respect, helping each other, and a sense of togetherness.